Empowerment Leadership in Improving Teacher Motivation and Performance in Educational Environments - Wahyuti, Yuli; Boussanlègue, TCHABLE (PPSDP International Journal of Education, 2025)
This article explores the concept of Empowerment Leadership in the context of education, particularly in enhancing teachers’ performance. Empowerment Leadership is a leadership style that focuses on empowering individuals by granting autonomy, trust, and opportunities for development in decision-making processes. The primary aim of this article is to identify how the implementation of Empowerment Leadership can influence teacher motivation, commitment, and performance in educational settings. By fostering collaboration, open communication, and recognizing teachers’ initiatives and creativity, it is expected to create a more productive and innovative work environment. The findings suggest that leaders who apply Empowerment Leadership can cultivate a positive work climate, strengthen a sense of responsibility, and improve teaching quality, ultimately contributing to enhanced teacher performance. This article aims to serve as a reference for educational practitioners in developing more effective leadership strategies to achieve better educational outcomes.